Effects of reduced training on muscular strength and endurance in competitive swimmers - Neufer, P. D.; Costill, D. L.; Fielding, R. A.; Flynn, M. G.; Kirwan, J. P. (Medicine & Science in Sports & Exercise, 1987)
Following five months of competitive training (9,000+ yards, 6 days per week) which produced a 14.3% increase in VO2 over an entire season, three groups of eight male swimmers performed four weeks of either reduced training (3,000 yards per session) or inactivity (RT0). One group (RT3) did three sessions while another (RT1) did one session per week. This study suggests that aerobic capacity was retained in well-trained swimmers with three workouts a week while applied power was reduced. Strength measured on the swim bench was unchanged which suggests that its measurements are not specific to swimming. Swimming power is diminished by the reduction in workout frequency. The reduction of workload to 30% of the change training load is sufficient to maintain aerobic capacity. Since all groups lost a similar amount of power, it is possible that a higher frequency of training is necessary to maintain applied strength in the water.